Knossos myth, history and archaeology - Whitley, James ca. 20./21. Jh (Bloomsbury Academic, 2024)
"Knossos is one of the most important sites in the ancient Mediterranean. It remained amongst the largest settlements on the island of Crete from the Neolithic until the late Roman times, but aside from its size it held a place of particular significance in the mythological imagination of Greece and Rome as the seat of King Minos, the location of the Labyrinth and the home of the Minotaur."
Literaturverzeichnis: Seite 193-217, Index
Keywords: Geschichte; Archäologische Stätte; Knossos; Knossos (Extinct city) / Antiquities